The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.4236/wjcd.2023.131005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mindful Meditation, Physical Activity, and Diet to Reduce the Risk to Develop or Reduce Severity of Cardiovascular Diseases in Saudi Arabia: A Systematic Review

Abstract: Background: Cardiovascular Disease (CVD) is one of the leading chronic diseases in Saudi Arabia (SA) that cause disability and death. CVD predisposition risk varies according to age, gender, education, socioeconomic factors, and place of residency. In addition, CVD risk factors include physical inactivity, sedentary lifestyle, saturated fatty acid high diet, smoking, and stress. Aim: This is a systematic review study that aims to determine the effect of mindful mediation, physical activity, and diet on CVD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Statistics indicate that roughly 3.2million deaths annually can be attributed to inadequate levels of physical activity (270), with healthcare expenses amounting to $117 billion yearly, attributed to conditions resulting from a lack of exercise (271). People who adopt a sedentary lifestyle and fail to engage in regular physical activity are more prone to the development of cardiovascular disease (272), and who are less active face a 30-50% higher risk of developing high blood pressure (273). The researchers predicted that lack of exercise was responsible for 12% of myocardial infarctions (MI), a risk proportion that fell within high blood pressure (18%), CVD cases (6%) and diabetic mellitus (10%) recognized risk factors for heart disease whose incidence is also inversely related to physical activity levels (274,275).…”
Section: Exercisementioning
confidence: 99%
“…Statistics indicate that roughly 3.2million deaths annually can be attributed to inadequate levels of physical activity (270), with healthcare expenses amounting to $117 billion yearly, attributed to conditions resulting from a lack of exercise (271). People who adopt a sedentary lifestyle and fail to engage in regular physical activity are more prone to the development of cardiovascular disease (272), and who are less active face a 30-50% higher risk of developing high blood pressure (273). The researchers predicted that lack of exercise was responsible for 12% of myocardial infarctions (MI), a risk proportion that fell within high blood pressure (18%), CVD cases (6%) and diabetic mellitus (10%) recognized risk factors for heart disease whose incidence is also inversely related to physical activity levels (274,275).…”
Section: Exercisementioning
confidence: 99%
“…Among them, two were cross-sectional studies in Riyadh city, conducted on patients in primary healthcare centers, and conducted in primary healthcare centers and universities and online [7,21]. There was a prospective urban rural epidemiology study that compared rural and urban areas and found more physical inactivity-related risks in rural areas [24]; one included Hail City residents [30], one was a cross-sectional study including the general population in Abba [27], two were systematic literature reviews [25,26], one was conducted among nurses [28], and one was conducted during COVID-19 quarantine among medical students at Tabuk University [22]. Physical inactivity or low physical activity was reported in up to 69.4% of the population, mostly among Saudi women, with up to 1.5 odds of CVD [24].…”
Section: Physical Inactivity/sedentary Lifementioning
confidence: 99%
“…The report by Saudi Health Council showed that a diet heavy in fat and poor in fiber was among the risk factors for CVD among a third of the Saudi population, together with other factors reported above [10]. Other six studies, including two cross-sectional studies, one community-based study, one including hypercholesterolemia patients, one among female university employees and one including nurses [19,23,28], two systematic literature reviews [25,26], and one cohort involving the general population [24] reported that unhealthy diet was a risk factor for CVD. One study reported more unhealthy diets among rural residents than urban residents and among young Saudis [24].…”
Section: Unhealthy Dietmentioning
confidence: 99%